Solving Hybrid Nanofluid Flow Over a Permeable Shrinking Cylinder Using Shooting Technique - Mat Yusof, Nur Syazwani; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2024)
This study explores the flow and heat transfer characteristics of Cu-Al2O3/water hybrid nanofluid over a permeable shrinking cylinder using the shooting technique. The research employs the Runge-Kutta-Fehlberg (RKF45) method in Maple to provide numerical solutions for the governing nonlinear partial differential equations. In the validation phase, the outcomes are compared with both an exact analytical solution and numerical values across various cases. Results indicate that the hybrid nanofluid exhibits lower heat transfer than alumina-water nanofluid due to increased suction. The heat transfer rate varies with alumina and copper volumetric concentrations, with the least alumina concentration yielding the highest rate. The addition of alumina and copper volumetric concentration reduces the heat transfer rate. Temperature profile correlates positively with curvature parameter and Eckert number but inversely with the magnetic parameter. Velocity profile escalates with an increase in the magnetic parameter. Basically, this study offers insights into the heat transfer of hybrid nanofluids over a permeable shrinking cylinder. This research contributes to understanding nanofluid heat transfer and provides a benchmark for future investigations into the influence of physical parameters and diverse hybrid materials.